RETRACTED: QbD-based rivastigmine tartrate-loaded solid lipid nanoparticles for enhanced intranasal delivery to the brain for Alzheimer's therapeutics - Arora, Deepshi; Bhatt, Shailendra; Kumar, Manish; Verma, Ravinder; Taneja, Yugam; Kaushal, Nikita; Tiwari, Abhishek; Tiwari, Varsha; Alexiou, Athanasios; Albogami, Sarah; Alotaibi, Saqer S.; Mittal, Vineet; et al. (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is a neurodegenerative disease that affects a wide range of populations and is the primary cause of death in various countries. The treatment of AD is still restricted to oral conventional medicines that act only superficially. Fabrication of intranasal solid lipid nanoparticulate system for uptake of therapeutic agents will act as a convincing approach with limited off-site toxicity and increased pharmacological activity. The objective of this study was to formulate, optimize and evaluate the efficiency of Rivastigmine tartrate (RT) loaded intranasal solid lipid nanoparticles (SLNs) employing the solvent evaporation-diffusion method. To optimize the formulation parameters, the Central Composite Design (CCD) was used. Lipid concentration (X1) and surfactant concentration (X2) were considered independent variables, while particle size (Y1), percentage entrapment efficiency (Y2), and percentage drug release (Y3) were considered responses. The solid lipid was glyceryl monostearate, while the surfactant was polysorbate 80. The optimized formulation has a particle size of 110.2 nm, % entrapment efficiency of 82.56%, and % drug release of 94.86%. The incompatibility of drug excipients was established by Differential Scanning Calorimetry (DSC) and Fourier Transform infrared spectroscopy (FTIR). Nasal histopathology tests on sheep mucosa revealed that the developed SLNs were safe to utilize for intranasal delivery with no toxicity. Ex vivo permeation investigations revealed that the flux and diffusion coefficients for RT-solid lipid nanoparticles and RT solution were 3.378 g/cm2 /h and 0.310-3 cm2 /h, respectively. Stability studies demonstrated that the developed SLNs were stable when stored under various storage conditions. The viability and vitality of adopting a lipid particle delivery system for improved bioavailability via the intranasal route were also established in the in vivo pharmacokinetics investigations. According to histopathological and pharmacokinetic investigations, the developed formulations were safe, non-lethal, efficient, and robust. These results suggest the potentiality provided by Rivastigmine tartrate loaded solid lipid nanoparticles for nasal delivery.